2019
DOI: 10.1097/mao.0000000000002108
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Intratympanic Methylprednisolone Versus Gentamicin in Patients With Unilateral Menière's Disease

Abstract: Objectives: 1) To determine whether long term (>48 months) symptomatic vertigo control is sustained in patients with Menière's disease from a previous comparative trial of intratympanic methylprednisolone versus gentamicin, and 2) if the two treatments remain non significantly different at long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…36,37 However, the data in the literature are inconsistent as to its efficacy at 5 years, which varies from 70% to 81%. 38,39 In comparison to VN its efficacy rate always seems lower, whether it is at 2 years (75% in the case of ITG vs 95.8% in the case of VN for Colletti et al 40 ) or at more than 2 years (81% at 2.7 years in the case of ITG vs 93% at 4.9 years in the case of VN for Morel et al 15 ).…”
Section: Discussionmentioning
confidence: 98%
“…36,37 However, the data in the literature are inconsistent as to its efficacy at 5 years, which varies from 70% to 81%. 38,39 In comparison to VN its efficacy rate always seems lower, whether it is at 2 years (75% in the case of ITG vs 95.8% in the case of VN for Colletti et al 40 ) or at more than 2 years (81% at 2.7 years in the case of ITG vs 93% at 4.9 years in the case of VN for Morel et al 15 ).…”
Section: Discussionmentioning
confidence: 98%
“…These results are in accordance with those from Weckel et al 23 who retrospectively evaluated 25 patients treated with IT dexamethasone; they reported a satisfactory control of vertigo in 92% of the patients, and this protocol achieved control of vertigo in 70% of patients at 2 years. Harcourt et al 24 suggested IT methylprednisolone as an effective treatment for the long-term control of vertigo attacks, without he known inner-ear toxicity associated with gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of dexamethasone ranged from 10 mg/dl to 40 mg/ml and frequency from 3 times one week to 2 times one month apart [ 9 , 12 15 ]. The concentration of methylprednisolone ranged from 40 mg/dl to 62.5 mg/ml and frequency from once a day to 2 times two weeks apart [ 9 , 10 , 16 18 ]. Thus, the IT delivery schedule is not settled so far, but it seems that more than one IT-injection should be delivered and is recommended.…”
Section: Intratympanic Corticosteroidsmentioning
confidence: 99%